Implementation of the Alef Education Learning Platform in English Language Subjects (Best Practice at MTs Negeri Gunungsitoli) - Lismaya Lubis; Azizah Hanum OK; Yusnaili Budianti (Yayasan Sembilan Pemuda Indonesia, 2026)
This study investigates the implementation of the Alef Education platform in English learning at MTs Negeri Gunungsitoli as a model of digital pedagogical innovation in Islamic secondary education. The research aims to: (1) describe the planning and integration process of Alef Education, (2) analyze its instructional practices, and (3) evaluate its pedagogical impact. A qualitative descriptive method with a case study design was applied. Participants included English teachers and students from grades VIII and IX. Data were collected through observation, interviews, and documentation, then analyzed thematically following Braun and Clarke’s framework. Results indicate that Alef Education enhances student engagement through interactive exercises, automated feedback, and curriculum alignment. Institutional support, teacher readiness, and learner motivation emerged as enabling factors, while limited internet connectivity and uneven digital literacy were key constraints. Effective practices include lesson plan integration, automated assessment use, and continuous teacher mentoring. The study concludes that Alef Education can improve English learning outcomes when supported by adequate ICT infrastructure, adaptive pedagogy, and sustained professional development.